ASSESSMENT OF ECONOMIC WORTH OF GREEN ROOF: A CASE STUDY IN PUTRAJAYA - Mohamad Hamzah, Firdaus; Mat Sulaiman, Mohd Khairul Azhar; Harun, Zambri; Kamari, Azwan; Abd Manaf, Muhammad Zaki (PLANNING MALAYSIA, 2023)
The current global temperature rise has affected local climate change issues and increased the energy usage for the building cooling process. Following this, the roof components have been identified to contribute the building heating effect due to exposure for more than 10 hours a day which at the same time secretes 70% of the sun's radiation. As an alternative, the green roof concept approach potentially reduces the effects of internal heat and operating costs of cooling the building while providing an investment return for the desired period. This study aims to measure the level of effectiveness of the building green roof concept on the building cooling rate and its profitability implications. Two objectives have been set. First, to compare the effects of concrete and green roof applications on energy consumption and operating costs for the cooling effects of air-conditioned buildings (active systems). Second, to evaluate the maintenance cost and profitability of applying the green-roofed building concept in terms of periodic return on investment. The findings of this study are seen to help the government and relevant agencies consider using the green roof concept in the physical construction of buildings in the future.